2007
DOI: 10.1007/s10750-007-9231-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental conditions on the seasonal variation of Microcystis cell density and microcystins concentration in San Francisco Estuary

Abstract: A bloom of the cyanobacteria Microcystis aeruginosa was sampled over the summer and fall in order to determine if the spatial and temporal patterns in cell density, chlorophyll a (chl a) concentration, total microcystins concentration, and percent microcystins composition varied with environmental conditions in San Francisco Estuary. It was hypothesized that the seasonal variation in Microcystis cell density and microcystin concentration was ecologically important because it could influence the transfer of tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 46 publications
10
79
0
Order By: Relevance
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 70%
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 70%
“…An earlier study result of Pan et al (2006) also revealed a similar result that the MC concentrations of all the samples were lower than 1 μg/L in western Fubao bay of the Dianchi Lake. Previous studies have reported that MCs in water samples were strongly correlated with environmental factors, such as TN (Graham et al, 2006), TP (Kotak et al, 2000), low stream flow and high WT (Lehman, 2008;Duong et al, 2012) and NO 3 − concentration (Mitsuhiro et al, 2007). In contrast, according to Jungmann et al (1996), MC concentration was not correlated with any measured variables in a hypereutrophic reservoir in Germany.…”
Section: Explanation Of the Dynamics Of Extracellular MC Concentrationsmentioning
confidence: 99%
“…(Jacoby et al 2000;Lehman et al 2005Lehman et al , 2008 and the establishment of nuisance aquatic vegetation (largely E. densa and Eichhornia crassipes) (Brown and Michniuk 2007;Sousa et al 2009Sousa et al , 2010Yarrow et al 2009). Stands of E. densa alter the physical structure of Delta channels and support the colonization of non-native fishes such as sunfish (Centrarchidae), which are often able to outcompete or prey upon native fishes (See 2.30 Structure, below) Grimaldo et al 2004;Nobriga et al 2005;Nobriga and Feyrer 2007;Ferrari et al 2014).…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Blooms can continue until they are broken up by increased flows, turbulence from wind-causing mixing-or drawdown of nutrients by the phytoplankton bloom itself. (Lehman et al 2008). Harmful algal blooms may be related to high concentrations of NH 4 (Lehman et al 2010).…”
Section: Diagram 2-nutrient Supply To Phytoplanktonmentioning
confidence: 99%